2020
DOI: 10.1159/000508561
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Hepcidin and Reticulocyte Haemoglobin during Septic Shock

Abstract: Septic shock, a serious consequence of disseminated infection that has a high mortality, is due to a dysregulated, severe immune response triggered by the infection. Acute phase reactants play key roles in sepsis, for example, hepcidin regulating iron metabolism. Reticulocyte haemoglobin (Ret-He) depends on available iron in blood, indirectly regulated by hepcidin. This study aimed at exploring rapid changes in hepcidin and Ret-He in patients with septic shock receiving adequate antibiotic treatment. Fifteen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
2
15
1
Order By: Relevance
“…We have consistently found that plasma hepcidin levels have a superior predictive value in distinguishing bacterial from viral infections, particularly in bacterial enteritis and urinary tract infections in FC, and are correlated to CRP levels [ 45 ]. Furthermore, Olinder et al showed that patients with septic shock acquiring appropriate antibiotic treatment demonstrated a rapid and prompt decline of hepcidin within the first 24 h [ 46 ]. In addition, plasma hepcidin levels have a good predictive value for the 28-day ICU mortality of septic patients [ 47 ] and can reflect bacteremia in critical patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have consistently found that plasma hepcidin levels have a superior predictive value in distinguishing bacterial from viral infections, particularly in bacterial enteritis and urinary tract infections in FC, and are correlated to CRP levels [ 45 ]. Furthermore, Olinder et al showed that patients with septic shock acquiring appropriate antibiotic treatment demonstrated a rapid and prompt decline of hepcidin within the first 24 h [ 46 ]. In addition, plasma hepcidin levels have a good predictive value for the 28-day ICU mortality of septic patients [ 47 ] and can reflect bacteremia in critical patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the pentraxin family of proteins and binds to lysophosphatidylcholine on the surface of dead cells and bacteria, an interaction that activates the complement system and promotes subsequent phagocytosis [2, 3]. Severe inflammation and sepsis are characterized by a complex series of events that affect individuals to various extents, for example depending on the causative agent and underlying disease [4-7]. Long CRP has been used as a sensitive serum biomarker to follow the course of diseases characterized by inflammation.…”
mentioning
confidence: 99%
“…Sepsis is a condition that continues to plague individuals worldwide, and the Journal of Innate Immunity has published many articles reflecting different perspectives on this "syndrome," not least in recent years [12][13][14][15]. Yang et al [16] present a study in this issue, showing that double-stranded RNA-dependent kinase R (PKR), an intracellular sensor of viral infection, plays a key role in host defense during polymicrobial sepsis .…”
mentioning
confidence: 99%